Integrative Structural, Functional and Aesthetic Rehabilitation of Fractured Non-vital Maxillary Central Incisor with Open Apex: A Case Report - Maddimsetti, Harshitha Ramana Priya; Kanumuri, Madhu Varma; Dalavai, Praveen; Mavidi, Jagapathi Babu; Ketavatu, Durga Prasad Naik; Redrouthu, Kalyani (International Journal of Dental Materials, 2025)
Anterior teeth, due to their prominent visibility during smiling, speech, and other facial expressions, are integral to dental aesthetics, phonetics, psychosocial confidence and self-esteem. Traumatic injuries sustained before the closure of the apex interrupt root development and result in incomplete apical closure. Management of fractured nonvital permanent anterior teeth with open apex remains challenging owing to thin radicular dentin and structurally compromised crowns, necessitating a strategic approach. This case report highlights a meticulously coordinated, conservative strategy to rehabilitate a fractured nonvital maxillary central incisor with an open apex. A 23-year-old male patient presented with a fractured, nonvital maxillary central incisor with an open apex resulting from trauma at the age of 9 years. Initial endodontic management includes access cavity preparation, followed by which the root canal system was thoroughly debrided using conventional cleaning and shaping protocols, augmented with laser-assisted disinfection to enhance microbial control and optimize canal cleanliness. Due to the presence of an open apex, a mineral trioxide aggregate (MTA) apical plug was placed to establish an apical seal, induce an artificial apical barrier and promote periapical healing. Given the thin root canal walls, a custom-fabricated anatomic post was created to provide reinforcement and improve internal adaptation, reducing the risk of root fracture. Advanced digital techniques were incorporated through intraoral scanning and CAD/CAM design, enabling precise fabrication of a zirconia crown, ensuring excellent fit, strength, and aesthetics. This case illustrates that combining biomaterials, laser technology and digital dentistry can provide a conservative structural, functional, and aesthetic outcome in the management of structurally compromised permanent anterior teeth with open apex.